Unicompartmental Knee Arthroplasty: Mobile Magic - Pandit, H; Murray, D; Dodd, C (2011)
Unicompartmental knee arthroplasty has many advantages over total knee arthroplasty, including better function, restoration of normal kinematics, and less morbidity. This paper outlines the design features, indications, contraindications, principles of surgical technique, and long-term results of the Oxford Knee, a mobile-bearing unicompartmental knee arthroplasty. Approximately 1 in 3 patients requiring a knee replacement are appropriate for the Oxford knee. The Oxford Group believes that this is a definitive and not a pre-total knee arthroplasty option provided that appropriate indications and correct surgical technique are used. © 2011 Elsevier Inc.